Review the Innovation of Manuchehr Neyestani in Poetic Elements of Ghazal - Nurya Yahu; Seif addin Abbarin; Barat Mohammadi (مطالعات زبانی و بلاغی)
Manuchehr Neyestani can be considered as one of the pioneers of the Persian modern sonnet (Ghazal). Hussein Monzavi considered him one of the pioneers of the Persian modern ghazal and believed that his place in the changes and developments of contemporary Ghazal, remains unknown. Neyestani's all-encompassing endeavor to achieve a new form in Ghazal has made him one of the first Ghazal poets that have taken a step in this direction. His efforts to expand the content and capacities of the Ghazal are also remarkable, and he has not paid much attention to the thematic clichés of traditional Ghazal and their repeated aesthetic criteria and has replaced individualism, realism, and subjectivism. he has also created new and innovative images based on individual and personal perspectives and inspired by the elements and characteristics of its time and Environment. In the poetic language, he has broken the hegemony of literary language and He has introduced colloquial and spoken words and expressions in a ghazal. The present study tries to examine and study the neyestani's modernities in the mentioned fields and to reveal the position of this poet in the dimensions of modernity in Ghazal.